Verbal polisemanisms in the lexical resource of kindergarten-age children - Ejsmunt-Wieczorek, Izabela (Interdyscyplinarne aspekty diagnozy i terapii logopedycznej, 2020)
This is another article in the series devoted to the word formation of the verb in speech ontogenesis. This time, the issue of terminological complexities related to the phenomenon of ambiguity in language was raised. Additonally, the polisemy-neosemantism relationship in the lexical resource of kindergarten children was shown, and an attempt was made to determine whether, in case of preschool children speech, we can talk about verbal lexical polisemy or only about neologisation (neosemanisation) of the language.